Antibacterial and antioxidative activity of the essential oil and seed extracts of Artocarpus heterophyllus for effective shelf-life enhancement of stored meat - Aizi Nor Mazila, Ramli; Sharifah Zafierah, Syed Badrulzaman; Hazrulrizawati, Abd Hamid; Prakash, Bhuyar (Blackwell Publishing Ltd., 2020)
This study was designed to examine the in vitro antimicrobial and antioxidant activity of the essential oil and various extracts processed from Jackfruit seed (Artocarpus heterophyllus). Seed extracts obtained from Jackfruit were tested for TPC and TFC, and the TPC of 34.48 ± 1.77 mg GAE/g extract was detected while TFC of 0.19 ± 0.004 mg QE/g extract was found significantly. Phytochemical screening of A. heterophyllus seed extracts using UPLC–QTOF/MS revealed the presence of eight compounds, representing (−)-Epiafzelechin-3-O-(6′′-O-acetyl)-β-D-allosepyranoside was the most abundant phenolic compound. Further samples were also subjected to a screening for their possible antioxidant activity using 2,2-diphenyl-1-picrylhydrazyl assay. DPPH analysis revealed that seed extract of A. heterophyllus has satisfactory radical scavenging capacity which could scavenge the free radicals produced during oxidation process in meat. The antioxidant activity can be observed for meat treated with seed extract as the TBA value was decreased in the samples on the addition of seed extract. However, in this study, seed extract treatment exhibited significant increase in MetMb content at 2 and 3 days of storage than in the control. The significance for all comparisons was determined at the p < .05 level. This result indicated that Jackfruit extract can be used commercially for meat shelf-life management.